Tax evasion and the law : a comparative analysis of the UK and USA - Bourton, Sam (Lecturer in law) (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book provides a critical and contemporary evaluation of the laws and enforcement policies pertaining to tax evasion in the United Kingdom (UK) and United States (US). Since the inception of taxes, revenue collection authorities around the world have attempted to address the seemingly perennial problem of individuals evading their tax liabilities. The financial crisis has shone a new light on the issue with an increased interest in using the criminal justice system as a means of addressing it in the UK. In sharp contrast to the UK, the US has a strong record of prosecuting crimes of tax evasion, whether committed by individuals or professional corporate facilitators. Providing an evaluation of the UK's tax evasion laws and enforcement policy, through a comparative approach, this work highlights insights provided by the US experience. In so doing, the book explores the interconnections between tax evasion and money laundering, identifying best practices, omissions, and areas for reform. The work will be a valuable resource for researchers, academics and policy-makers working in the areas of Financial Crime, Financial Law, Accountancy and Criminal Justice"--
A typology of tax evasion -- Combatting offshore tax evasion -- International cooperation in tax matters -- The Anti-money laundering legal framework and its Application to tax evasion offences -- Tax evasion legislation in the UK and US -- The enforcement of tax evasion legislation in the UK and US.
Keywords: Tax evasion -- Law and legislation -- Great Britain; Tax evasion -- Law and legislation -- United States; Tax evasion (International law); Money laundering -- Great Britain -- Prevention; Money laundering -- United States -- Prevention; LAW / Criminal Law / General; LAW / Business & Financial